Human Mesenchymal Stem Cell Based Intracellular Dormancy Model of Mycobacterium tuberculosis - Singh, Vipul K (Microbes Infect, 2020)
Understanding the biology of the tuberculosis pathogen during dormant asymptomatic infection, called latent tuberculosis is crucial to decipher a resilient therapeutic strategy for the disease. Recent discoveries exhibiting presence of pathogen’s DNA and bacilli in mesenchymal stem cells (MSCs) of human and mouse despite completion of antitubercular therapy, indicates that these specific cells could be one of the niches for dormant M. tuberculosis in humans. To determine if in vitro infection of human MSCs could recapitulate the in vivo characteristics of dormant M. tuberculosis, we examined survival, phenotype, and drug susceptibility of the pathogen in MSCs. When a very low multiplicity of infection (1:1) was used, M. tuberculosis could survive in human bone marrow derived MSCs for more than 22 days without any growth. At this low level of infection, the pathogen did not cause any noticeable host cell death. During the later phase of infection, MSC-residing M. tuberculosis exhibited increased expression of HspX (a 16-kDa alpha-crystallin homolog) with a concurrent increase in tolerance to the frontline antitubercular drugs Rifampin and isoniazid. These results present a human MSC-based intracelllular model of M. tuberculosis infection to dissect the mechanisms through which the pathogen acquires and maintains dormancy in the host.